Twice upon a time - Riley, James, 1977- ([Book two in the Half upon a time series], 2012)
Jack, of the village of Giant's Hand, is now accompanied by a prince as he continues trying to help a reluctant princess find her family, while also attempting to save a city full of fairies from a nameless curse.